(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to determine the role of ethical leadership in improving job satisfaction in the SFHRP. The study used a descriptive analytical approach based on the nature and objectives of the study to answer the study questions and test the hypotheses. A non-proportional stratified random sample of 500 individuals was taken from the study population, with (335) responses, representing 68%. The study tool was a questionnaire. The study results showed a moderate level of ethical leadership practices and quality of work life in the community studied. The hypothesis testing results indicated that the direct impact of ethical leadership on improving the quality of work life was statistically significant. The study made several recommendations, the most prominent of which were: the need to enhance work-life balance practices through organizational policies and ensure their implementation in a way that supports employees in maintaining a balance between personal life and work through stress management initiatives, time management, flexible schedules, remote work, expanding insurance coverage, and re-evaluating recognition mechanisms to better motivate individual performance.